Juridical Implications of Making of the Deed of Binding the Sale and Purchase of Land that Guarantees Individual Debt - Pratiwi, Eka (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
As social beings, humans need other humans to meet their needs. What's more, the human need for land continues to increase, in line with the increasing human population in Indonesia. Fulfilling the need for the land, can be done by carrying out sale and purchase transactions, and transferring rights over the land in order to obtain valid legal certainty in accordance with applicable regulations. The more important the need for land, the more problems that arise related to the transfer of land rights. As with the buying and selling process in general, besides the subject and object that must be clear, in buying and selling land there will also be rights and obligations that must be fulfilled by both parties. If one party is negligent and does not fulfill its obligations, as stated in the agreement. As described above, the author is interested in conducting research with the title